Comparação da carga microbiana em águas de pré-resfriamento e carcaças de frangos, após jornadas de trabalho de 8, 16 e 24 horas - Cavani, Ricardo [UNESP]; Schocken-Iturrino, Ruben Pablo [UNESP]; Garcia, Teresa Cristina Fernandes Lopes; de Oliveira, Adriana Cássia (FapUNIFESP (SciELO), 2010)
Poultry processing facilities are known for using a great amount of water, which is mainly used on carcasses chilling stage. In Brazil, meat regulations state that each chiller tank must be emptied, cleaned and sanitized every 8 working hours. The aim of the current study was to assess the microbial load of chiller water used in poultry immersion chilling system after 8, 16 and 24 working hours in order to evaluate the reduction of water changes and chiller sanitization. Conventional physicochemical and microbiological assays were done in water supply samples (n=69) to suppress interferences caused by freshwater addition; pre chilled (n=345) post chilled carcasses (n=345) and chiller water samples of the last stage (n=69). The results showed no significant differences on microbial load samples between the three shifts suggesting that the proposed reduction may be secure and reduces the volume of wastewater that would impact the environment, besides improving the rational use of processing time.
Comparison of microbial load in immersion chilling water and poultry carcasses after 8, 16 and 24 working hours
Keywords: Chiller water microbiological load; Immersion chilling; Poultry slaughterhouses